Is Fibular Sesamoidectomy a Viable Option for Sesamoiditis? A Retrospective Study - Leonardo V. M. Moraes MD; Jeffrey Pearson MD; Kyle Paul BS; Jianguang Peng MD; Karthikeyan Chinnakkannu MD; Haley McKissack BS; Aaradhana J. Jha MBBS, MS; Ashish Shah MD (Foot & Ankle Orthopaedics, 2019)
Category: Midfoot/Forefoot Introduction/Purpose: Although the first metatarsophalangeal joint sesamoids have biomechanical value in the foot, pathologic conditions of these sesamoids are a source of disabling pain for patients, particularly during toe-off. Underlying causes include acute fracture, acute separation of bipartite sesamoids, sesamoiditis caused by repetitive trauma, infection, chondromalacia, osteochondritis dissecans, and osteoarthritis. Nonoperative treatment is the initial standard of care and has satisfactory outcomes overall, but operative management may be indicated in cases of pain refractory to conservative management. Surgical management includes tendo-Achilles or gastrocnemius lengthening, dorsiflexion osteotomy at the base of first metatarsal, corrective osteotomies, fusions for fixed pes cavus foot. Sesamoidectomy is a relatively uncommon procedure but should be considered if 6- 12 months of conservative managements fail or if the patient experiences ongoing debilitating symptoms. Methods: A retrospective chart review was conducted at our institution from 2009-2018. Twelve patients diagnosed with fibular sesamoiditis were treated with sesamoidectomy. Baseline patient demographics as well as postoperative outcomes were recorded. All patients were initially treated for an extended period conservatively with orthotics, anti-inflammatory medications, physical therapy, limitation of activity and a trial of non-weight bearing. Despite these measures, symptoms persisted for these twelve patients - all of who then underwent fibular sesamoidectomy for their symptoms. The fibular sesamoidectomy was performed by one of the three fellowship trained foot and ankle surgeons. All surgeons used plantar approach with a longitudinal incision on the lateral edge of the first metatarsal fat pad. Postoperatively, patients were kept non–weight bearing for 2 weeks and in a post-op walking shoe for 6 weeks. Results: Average age of the patients was 38 years. Ten of twelve patients (83%) were female. Majority of the patients (10) had no history of trauma, only two referred forefoot injury in the past. Average follow-up was 35 months. Two patients had both hallux valgus and hallux rigidus. One had preexisting rheumatoid arthritis with involvement of the first MTP. MRI showed 5 of 12 (42%) of patients had avascular necrosis of the sesamoid based on magnetic resonance imaging. None of the patients developed cock-up deformity of the lesser toes or hallux varus deformity, clinically or radiologically. Two patients experienced transient neuritis, one developed a superficial infection, and one had painful postoperative scarring. Hallux varus deformity was not observed in any patients. None underwent reoperation. Conclusion: Our study contradicts earlier studies which associate sesamoidectomy with high incidence of complications, particularly hallux varus. But, most of these earlier reports focus on combinations of medial, lateral, and paired excision, rather than lateral excision alone, unlike our study. Hence, fibular sesamoidectomy can be a safe, viable procedure for patients who fail conservative measures for sesamoiditis. The plantar lateral approach allows for adequate exposure of the fibular sesamoid, repair of the plantar plate, and preservation of flexor hallucis brevis, and is beneficial in preventing the occurrence of hallux varus deformity.